Evaluation of Selected Physicomechanical Properties of SFRC according to Different Standards - Tereza Komárková; Jaromír Láník; Ondřej Anton (Advances in Materials Science and Engineering)
Steel fiber reinforced concretes are currently very popular, especially in the construction of industrial floors of warehouses and other halls with relatively large floor areas. However, it is important to mention that despite the rapid development of steel fiber reinforced concretes, the standards and regulations for their designing and testing have not been unified yet. This paper presents findings about the physicomechanical parameters of the steel fiber reinforced concretes manufactured by adding steel fibers into the truck mixer on the building site. The experimentally obtained results from the performed tests of tensile strength in bending according to various procedures are compared, and the suitability of the methods used is assessed according to these procedures.